Differential detection of conspecific-derived odorants by the two olfactory epithelia of the Senegalese sole (Solea senegalensis) - Velez, Zélia (2014)
The two olfactory epithelia of members of the family Soleidae sample two distinct water sources; the upper (right) side is in contact with the open water column whilst the lower (left) side is in contact with interstitial water. To evaluate whether there are differences in the sensitivities, and therefore functional roles, of the two epithelia the olfactory activity of conspecific-derived odorants was assessed in both using the electro-olfactogram (EOG). The upper nostril was significantly more sensitive to conspecific bile fluid, intestinal fluid and mucus than the lower nostril. Crude fractionation of these samples (solid-phase extraction with C18 and C2/ENV+ cartridges) revealed that olfactory activity in each body fluid was likely due to a mixture of compounds. In each case, the upper olfactory epithelium was significantly more sensitive than the lower. Similarly, olfactory sensitivity to a range of C24 and C27 bile acids was greater in the upper epithelium. These results suggest that intra-specific chemical communication is mediated mainly, if not entirely, by the upper olfactory epithelium. The odorants involved, and their functional roles, remain to be established.